Klasifikasi Persediaan pada Gudang Bahan Kemasan XYZ dengan Metode FSN Analysis (Fast, Slow, Non-Moving) Berdasarkan Turn Over Ratio (TOR) - Arifin, Chairunisa Az Zahra; Nugraha, Asep Erik; Winarno, Winarno (Engineering Faculty at Universitas Singaperbangsa Karawang, 2023)
Inventory is synonymous with warehouse, and storage grouping has an essential role in warehouse management to facilitate activities on products that occur in the warehouse before being sent to customers in the future. The problem with the XYZ packaging warehouse is that the different conditions of goods turnover cause storage in the packaging warehouse to become irregular. This study aims to classify inventory so that it is allocated better based on the speed of movement of goods. Quantitative data was obtained through observation, literature study, and company historical data. The method used is FSN Analysis, a classification based on an item consumption level into three categories. The results of data processing that show from this study were 17 items in the fast-moving category with a turnover ratio greater than 3 (TOR > 3), 14 items in the slow-moving category with a turnover ratio between three or less than three and one or more than one (3 ≤ TOR ≤ 1), and 2 items in the non-moving category with a turn over ratio of less than 1 (TOR < 1). FSN Analysis can improve warehouse management in controlling the storage of these goods in groups.